Investigations on Pressure Broadening Coefficients of NO Lines in the 1←0 Band for N2, CO2, Ar, H2, O2 and He - Sumit Agarwal; Leopold Seifert; Denghao Zhu; Bo Shu; Ravi Fernandes; Zhechao Qu (Applied Sciences, 2023)
A tunable diode laser absorption spectroscopy (TDLAS)-based spectrometer employing a mid-infrared (Mid-IR) interband cascade laser (ICL) was developed and used to determine pressure broadening coefficients of two NO absorption transitions at 1914.98 cm−1 and 1915.76 cm−1 in the fundamental (1←0) band (R11.5 Ω1/2 and Ω3/2) for CO2, N2, Ar, O2, He, and H2. For the first time, a reliable and consistent set of six different pressure-broadening coefficients for the NO line has been measured by a consistent approach covering pressures from 100 to 970 mbar at a temperature of 294 K. Air pressure broadening has been calculated based on N2 and O2 coefficients. The stated pressure-broadening coefficients for N2, CO2, Ar, H2, O2, He, and Air have relative errors in the 0.5–1.5% range. For CO2 and H2, broadening results of NO (1←0) band (R11.5 Ω1/2 and Ω3/2) lines are reported for the first time. The results are also compared to previously available literature data. It was found that the broadening coefficients for O2 and Air are in agreement with literature values, whereas results for Ar and He show larger differences.